Effect of cognitive restructuring counselling techniques in managing chemistry anxiety among senior secondary school students in Tambuwal Local Government, Sokoto State - Yahaya, Ishaka; Tambuwal, Nasiru Aliyu (Kashere Journal of Education, 2023)
This study focused on the effect of Cognitive-Restructuring counselling techniques in managing chemistry anxiety among Senior Secondary School in Tambuwal local government area of Sokoto State. The researcher employed quasi-experimental pre-test/post-test factorial design in which selected students were assigned to experimental groups and control group. The experimental groups were treated with cognitive restructuring counselling technique while the control group didn’t receive any treatment. The population of the study is 160 students with chemistry anxiety. 114 students were selected to participate in the study. Purposive sampling technique was used. The treatments were carried out within eight weeks of counselling sessions. Group counselling method was employed in the study. Each of the subjects was administered with pre-test/post-test research instrument. Validated instruments namely Derived Chemistry Anxiety Rating Scale (DCARS)) was used in generating response from the students. The researcher made use of dependent samples t-test to analysed hypothesis 1 and independent t-test was used to analysed hypothesis 2 tested at 0.05 level of significance. Results of this study shows that there was a significance differences in the effect of cognitive restructuring counselling technique on the pre-test/post-test means score on anxiety level among students with chemistry anxiety in Tambuwal local government. Equally there is no significant difference on the anxiety level between the group exposed to cognitive restructuring counselling technique and those in the control group in Tambuwal local government. Though there is difference but not significant. Based on these findings, it was recommended that counsellors could use Cognitive- Restructuring treatment as a technique to reduce anxiety in Chemistry among Secondary School Students since it has been identified as effective.